PSO Based Path Planning Approach for Multi Service Robots in Dynamic Environments - Baygin, Nursena; Baygin, Mehmet; Karakose, Mehmet (Ieee, 2018)
Creating a path planning for multi-robot traveling in dynamic environments is a very difficult problem. In this paper, it is aimed to create the most appropriate path plan for reaching the target by overcoming the obstacles encountered by the service robots. For this, particle swarm optimization (PSO) based navigation is proposed. Multi-robot in the same environment have been communicated with each other in order to form the path plan. The robot positions and suitability functions that are constantly updated ensure the best results. This study was designed to simulate Virtual Reality Educational Pathfinders (VREP) in a simulated environment and to work synchronously with the codes created in MATLAB. Looking at the experimental results, it is observed that the proposed method provides an effective solution to the path planning problem.
International Conference on Artificial Intelligence and Data Processing (IDAP) -- SEP 28-30, 2018 -- Inonu Univ, Malatya, TURKEY
Keywords: Service Robot; Particle Swarm; Multi robot; VREP; Navigation